2018
DOI: 10.1002/cncr.31536
|View full text |Cite
|
Sign up to set email alerts
|

Timing of palliative care needs reporting and aggressiveness of care near the end of life in metastatic lung cancer: A national registry‐based study

Abstract: There is a clear association between the timing of palliative care needs reporting and the aggressiveness of care near the end of life. Cancer 2018;124:3044-51. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
11
1
2
Order By: Relevance
“…23,29 A French study in patients who died of metastatic lung cancer showed that end-of-life care was less aggressive the earlier palliative care needs were reported in their EPRs: patients sooner stopped with anticancer treatment and they underwent less often invasive ventilation. 30 In patients with pancreatic cancer in the last 30 days of life who were referred to a palliative care service, those with an early referral to a palliative care team visited the ED less often and were less often hospitalized. 31 It thus seems that when palliative care is integrated into oncology care, patients with ST are at a lower risk of aggressive end-of-life care.…”
Section: Discussionmentioning
confidence: 99%
“…23,29 A French study in patients who died of metastatic lung cancer showed that end-of-life care was less aggressive the earlier palliative care needs were reported in their EPRs: patients sooner stopped with anticancer treatment and they underwent less often invasive ventilation. 30 In patients with pancreatic cancer in the last 30 days of life who were referred to a palliative care service, those with an early referral to a palliative care team visited the ED less often and were less often hospitalized. 31 It thus seems that when palliative care is integrated into oncology care, patients with ST are at a lower risk of aggressive end-of-life care.…”
Section: Discussionmentioning
confidence: 99%
“…Another strength of this study is the collection of data from clinical records giving access to the accurate timing of the first intervention of the palliative care team which is not recorded in hospital administrative database [28]. This allowed to describe large variations in the timing of referral to palliative care teams across centres and to analyse the accurate association between this intervention and the indicators of intensity of care.…”
Section: Discussionmentioning
confidence: 99%
“…9,12 In people with cancer, Chronic Obstructive Pulmonary Disease and Chronic Heart Disease, recognition of palliative care needs is associated with better quality of life, contacts with primary care services, more chances to die at home and avoidance of overly aggressive treatment near the end of life including hospital admissions. [13][14][15] The extent to which people with dementia are identified as having palliative care needs, and the benefits of this, are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesised that identification of palliative care needs would be associated with fewer hospital admissions close to death, and with a higher number of community palliative care team contacts based on results from previous studies. [13][14][15]…”
Section: Introductionmentioning
confidence: 99%